2010
DOI: 10.1007/s10439-010-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Abdominal Aortic Aneurysm Geometry

Abstract: Recent studies have shown that the maximum transverse diameter of an abdominal aortic aneurysm (AAA) and expansion rate are not entirely reliable indicators of rupture potential. We hypothesize that aneurysm morphology and wall thickness are more predictive of rupture risk and can be the deciding factors in the clinical management of the disease. A non-invasive, imagebased evaluation of AAA shape was implemented on a retrospective study of 10 ruptured and 66 unruptured aneurysms. Three-dimensional models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 32 publications
5
105
0
4
Order By: Relevance
“…Consistently, in hypothetical aneurysm models [56] found that the inflection regions are subject to the highest stress. Thus, the AAA shape, size, and wall thickness distribution altogether contribute to the complex wall stress distribution which is markedly evolving as the AAA enlarges [4]. We submit that morphological features alone may not be sufficient to determine the rupture potential.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Consistently, in hypothetical aneurysm models [56] found that the inflection regions are subject to the highest stress. Thus, the AAA shape, size, and wall thickness distribution altogether contribute to the complex wall stress distribution which is markedly evolving as the AAA enlarges [4]. We submit that morphological features alone may not be sufficient to determine the rupture potential.…”
Section: Discussionmentioning
confidence: 93%
“…7). Those geometrical features are suggested as diagnostic tools in the assessment of AAAs rupture potential [4,36]. Furthermore, Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A semi-automatic methodology was followed to segment and create the masks for the three domains (i.e., lumen, intra luminal thrombus (ILT), and AAA wall). The lumen was automatically segmented using an intensitybased threshold technique that differentiates blood from the surrounding tissues in the CT image [31][32][33]. The ILT was manually segmented, while a uniform AAA wall was developed by dilation of the lumen-ILT boundary by two pixels after performing a combination of Boolean operations on the masks.…”
Section: Clinical Image Acquisition and 3d Reconstructionmentioning
confidence: 99%
“…Initial studies have used uniform wall thickness in their attempt to characterize aneurysm shape. Although wall thickness was not one of the highest ranked features chosen with the feature selection algorithm based on the   test, its effect on aneurysm rupture cannot be ignore [45]. Typical values of wall thickness (t) in aneurysmatic arteries are ranged from 0.5 to 1.5 mm [46].…”
Section: Morphological Biodeterminants Mbdsmentioning
confidence: 99%